TWO WAYS COMUNICATION BASED FAMILY EMPOWERMENT CONCEPT TO MAINTAIN THE ECONOMY AND WALFARE OF RETIRED TKI FAMILY AT ARJOWILANGON - Luluk Dwi Kumalasari (Prodi Sosiologi FISIP Universitas Teuku Umar, 2015)
Migration phenomenon by Indonesian migrant workers (TKI), bring significant influence toward the change of their family. Influence of this change within the family as the cause of migration, either bring the better economy and welfare or, a devastated and disorganized family.The effort to empower retired TKI family means to improve TKI family using existing resources, opportunity, skills and knowledge to elevate their household economy and welfare. However, there are still many cases of problematic TKI families, but there are also families that can manage their household income once they return home.As the basis area of east java migrant workers, Malang Regency specifically Arjowilangun Village become one of the interesting locust to examine the case of TKI Family empowerment in order to ensure their security and welfare of their family based on two way comunication. The model of two way communication, certainly undeniable to achieve desirable outcome by family. This model used to deliberate case retired TKI family at Arjowilangun village.This research attempt to elaborate the phenomenon of retired TKI Family whom able to manage their household income and improve their family welfare, by using the concept of TKI family empowerment to secure their household economy and family welfare based on two way comunicationmodel. The result of this research hope to serve the conceptual purpose or example for retired TKI family to enhance their economy and family welfare. On empirical basis, the two way comunication model were effectively applied by the member of Retired TKI Family. Horizontally the outcome of this communication would create more relax and intimate. Other from that outcome, the economic enterprise with the involvement of retired TKI could stimulate the sustainable household income and further, the long term economic stability.